STRATEGI PEMASARAN UMRAH PADA PT. SINAI TOUR & TRAVEL DALAM MENINGKATKAN MINAT JAMAAH BUKITTINGGI - Siti Aisyah; Tartila Devy (Jurnal Ekonomi dan Bisnis, 2025)
The problem in this study is the ineffectiveness of the marketing strategy implemented, particularly in the aspects of a lack of product variation, an office location that is not strategically placed, and promotions that have not been maximized, resulting in many people not being aware of PT. Sinai Tour and Travel Bukittinggi branch. This study aims to analyze the marketing strategy implemented by PT. Sinai Tour and Travel Bukittinggi branch in an effort to attract the interest of potential pilgrims from Bukittinggi. The method used in this study is descriptive qualitative, collecting primary data through interviews, observations, and questionnaires at PT. Sinai Tour and Travel Bukittinggi branch, as well as secondary data from written sources such as books. The focus of this research is on the marketing mix strategy, which includes the 7P elements: Product, price, place, promotion, people, process, and physical evidence. The research findings indicate that although the products and facilities offered are quite attractive, there are some challenges that need to be addressed, such as the less strategic office location and the under-optimized promotion efforts. Other findings reveal that the affordable umrah package prices and high-quality services are the company’s strengths. However, the promotion aspect still requires more attention to enhance competitiveness amidst the intense competition in the hajj and umrah travel business in Bukittinggi.